Expression of DAP12 and its Triggering Co-Receptor TREM2 Plays a Key Role in Regulation of Liver DC Function and Control of Liver Ischemia-Reperfusion Injury. (July 2018) - Nakao, Toshimasa; Ono, Yoshihiro; Dai, Helong; Perez-Gutierrez, Angelica; Camirand, Geoffrey; Huang, Hai; Geller, David A; Thomson, Angus W
Abstract : Background: Liver interstitial dendritic cells (DCs) have been implicated in the control of liver ischemia/reperfusion injury (IRI) and in the induction of liver transplant tolerance. However, mechanisms underlying these regulatory functions of liver DCs remain unclear. We have shown previously that the transmembrane adaptor protein DNAX-activating protein of 12 kDa (DAP12) is a negative regulator of mouse DC maturation. In this study, we focused on the role of DAP12 and its associated triggering receptor, triggering receptor expressed on myeloid cells 2 (TREM2) in the regulation of both mouse and human liver DC function and the role of DAP12 in regulation of liver IRI. Materials and Methods: DAP12, TREM2, NFkB and T cell co-stimulatory or co-inhibitory molecule expression by freshly-isolated B6 mouse or normal human liver DCs was determined by flow cytometry, image stream and RT-PCR analysis. T cell proliferative responses were determined by CFSE-MLR and cytokine production by cytokine bead array analysis. DAP12-/- mice were bred from pairs provided by Dr. Marco Colonna, Washington University School of Medicine. Wild-type (WT) C57BL/6 (B6) and TREM2-/- mice were purchased from The Jackson Laboratory. Liver warm IRI was induced in DAP12-/- or WT mice by 1 hour 70% clamp. Liver enzyme (ALT) levels, inflammatory cytokine production and liver injury were quantified following 6 hours reperfusion. Results: Both DAP12 and TREM2 were expressed at comparatively high levels by mouse and human liver DCs, while flow analysis revealed co-expression of DAP12 and TREM2 by 75+/- 3.5 % of human liver DCs. Mouse DCs lacking DAP12 or TREM2 exhibited increased levels of NFkB activation, co-stimulatory molecule expression, proinflammatory cytokine production and T cell stimulatory function. Silencing DAP12 expression in human liver DCs using siRNA also led to enhanced T cell stimulatory activity. Notably, unlike normal control WT liver DCs, DAP12-/- liver DCs failed to inhibit T cell proliferative responses to aCD3/CD28 stimulation. In vivo, DAP12-/- mice subjected to liver IRI exhibited enhanced liver injury, accompanied by evidence of enhanced liver DC activation. Conclusions: Our data reveal a close association between the expression of DAP12 and its triggering receptor TREM2 by murine and human liver DC. DAP12 negatively regulates liver DC function and promotes their ability to inhibit inflammatory responses. Absence of DAP12 results in augmented liver IRI associated with enhanced liver DC activation. National Institute of Health grant R56 AI126377 (to AWT).National Institute of Health grant R01 HL 130191 (to AEM).